Adjunctive vitamin D for treatment of active tuberculosis in India: a randomised, double-blind, placebo-controlled trial. Issue 5 (May 2015) - Daley, Peter; Jagannathan, Vijayakumar; John, K R; Sarojini, Joy; Latha, Asha; Vieth, Reinhold; Suzana, Shirly; Jeyaseelan, Lakshmanan; Christopher, Devasahayam J; Smieja, Marek; Mathai, Dilip
Summary Background Vitamin D has immunomodulatory effects that might aid clearance of mycobacterial infection. We aimed to assess whether vitamin D supplementation would reduce time to sputum culture conversion in patients with active tuberculosis. Methods We did this randomised, double-blind, placebo-controlled, superiority trial at 13 sites in India. Treatment-naive patients who were sputum-smear positive, HIV negative, and had pulmonary tuberculosis were randomly assigned (1:1), with centrally labelled, serially numbered bottles, to receive standard active tuberculosis treatment with either supplemental high-dose oral vitamin D3 (four doses of 2·5 mg at weeks 0, 2, 4, and 6) or placebo. Neither the patients nor the clinical and laboratory investigators and personnel were aware of treatment assignment. The primary efficacy outcome was time to sputum culture conversion. Analysis was by modified intention to treat. This trial is registered with ClinicalTrials.gov, number NCT00366470. Findings Between Jan 20, 2010, and Aug 23, 2011, we randomly assigned 247 participants to the vitamin D group (n=121) or the placebo group (n=126), of whom 211 participants (n=101 and n=110, respectively) were included in the primary efficacy analysis. Median time to culture conversion in the vitamin D group was 43·0 days (95% CI 33·3–52·8) versus 42·0 days (33·9–50·1) in the placebo group (log-rank p=0·95). Three (2%) patients died in the vitamin D group and one (1%) patient died in the placebo group; no death was considered attributable to the study intervention. No patients had hypercalcaemia. Interpretation Our findings show that vitamin D supplementation did not reduce time to sputum culture conversion. Further studies should investigate the role of vitamin D in prevention or reactivation of tuberculosis infection. Funding Dalhousie University and Infectious Diseases Training and Research Centre.